Вплив внутрішніх механічних напружень і квантово-розмірного ефекту на ефективність сульфідної електронної пасивації GaAs - Венгер, Є.Ф.; Матвеєва, Л.О.; Колядіна, О.Ю.; Клименко, А.П. (Видавничий дім "Академперіодика" НАН України, 2007)
We have investigated the real and chemically sulfided gallium arsenide surfaces by the electroreflectance method in the E0-spectral region. On the basis of quantitative analysis of the experimental data, the flat band potential, energies of quantized levels, width of a quantum well, and the intrinsic mechanical stresses depending on sulfiding conditions are determined. We have ascertained optimal conditions for the improvement of the electron parameters of the substrate-sulfide film interface on the electron passivation of GaAs.